A kinetic study of a membrane anaerobic reactor (MAR) for treatment of sewage sludge - Abdullah, Abdul Ghani Liew; Idris, Azni; Ahmadun, Fakhru'l-Razi; Baharin, Badlishah Sham; Emby, F.; Megat Mohd Noor, Megat Johari; Nour, A. H. (Elsevier, 2005)
The application of kinetic models (Monod, Contois and Chen & Hashimoto) and overall microbial kinetic on the membrane anaerobic reactor (MAR) for treatment of sewage sludge was investigated. The system consists of a cross-flow ultrafiltration membrane and six steady states were attained over a range of mixed liquor suspended solids of 12,760-21,800 mg/l. The results of all six steady states were successfully fitted above 98% for three known kinetics. The growth yield coefficient, Y, was found to be 0.74 gVSS/gCOD while the specific microorganism decay rate was 0.20 d-1. The k values were in the range of 0.350-0.519 gCOD/gVSS.d and μmax values were between 0.259 and 0.384 d-1. The COD removal efficiency was 96.5-99% with HRT of 7.8 days. The methane gas yield was between 0.19 l/g COD/d to 0.54 l/g COD/d when the organic loading rate increased from 0.1 kg COD/m3/d to 10 kg COD/m3/d. The system efficiency was greatly influenced by SRT and OLRs. Membrane flux rate deterioration was observed from 62.1 l/m2/h to 6.9 l/m2/h due to membrane fouling.